Comprehensive insights of pretreatment strategies on the structures and bioactivities variation of lignin-carbohydrate complexes - Su, Chen; Wang, Xiu; Deng, Yongjun; Tian, Zhongjian; Huang, Chen; Fang, Guigan (Frontiers in Bioengineering and Biotechnology, 2024)
The lignin-carbohydrate complex (LCC) displays great potential in vast industrial applications due to its unique structural features and bioactivities. However, the elucidation of how various pretreatment methods affect the structure and bioactivities remains unaddressed. Herein, the effects of different pretreatment strategies on the structure alterations and bioactivity variations of LCC were comprehensively investigated. The results showed that compared to physical or chemical pretreatments, biological pretreatment was the most effective approach in improving the bioactivities of LCC. The LCC from biological pretreatment (enzymatic hydrolysis, ELCC4) had more functional groups while the lower weight-average molecular weight (Mw) and polydispersity index (PDI) were well-endowed. The highest antioxidant abilities against ABTS and DPPH of ELCC4 were high up to 95% and 84%, respectively. Furthermore, ELCC4 also showed the best ultraviolet (UV)-blocking rate of 96%, which was increased by 6% and 2% compared to LCC8 (physical pretreatment) and LLCC4 (chemical pretreatment). This work prospectively boosts the understanding of pretreatment strategies on the structures and bioactivities variation of LCC and facilitates its utilization as sustainable and biologically active materials in various fields.